2016
DOI: 10.1080/09540253.2016.1185094
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a professional: gendered knowledge in the (self-)positioning of skin and spa therapy students

Abstract: The self-archived postprint version of this journal article is available at Linköping University Institutional Repository (DiVA): http://urn.kb.se/resolve?urn=urn:nbn:se:liu:diva-143647 N.B.: When citing this work, cite the original publication. This is an electronic version of an article published in: Bredlöv, E., (2017), Constructing a professional: gendered knowledge in the (self-)positioning of skin and spa therapy students, Gender and Education, 29 (7) Constructing a professional: Gendered knowledge in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
(17 reference statements)
2
2
0
Order By: Relevance
“…This appears to be partly rooted in a scientific discourse of the learning content, and partly in the feminine ideal of a caring discourse. The use of a scientific discourse to self-position in a predominantly feminine vocation is in line with findings by Bredlöv (2017). We also found that boys tended to position themselves at some distance from the female caring discourse in this setting, and relied more than girls on the scientific discourse.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This appears to be partly rooted in a scientific discourse of the learning content, and partly in the feminine ideal of a caring discourse. The use of a scientific discourse to self-position in a predominantly feminine vocation is in line with findings by Bredlöv (2017). We also found that boys tended to position themselves at some distance from the female caring discourse in this setting, and relied more than girls on the scientific discourse.…”
Section: Discussionsupporting
confidence: 88%
“…The most striking conclusion of this study is that a caring discourse can be entwined, for female students, not only with discourses and activities related to consumption work and relational work with people, but also those related to working with machines. This extends previous findings that a caring discourse is important in VET contexts associated with consumption rather than production, including spa and skin therapy (Bredlöv 2017) and HSC (Rehn and Eliasson 2015). The relatively strong emphasis on being a female student and becoming a female worker through being and becoming (cf.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations